Manajemen Kesiswaan Dalam Mengimplementasikan Nilai-nilai Moderasi Beragama Melalui Pendidikan Karakter - Acep Rizki Al Fathir (Yayasan Al-Afif, 2025)
Religious moderation is an approach that emphasizes tolerance, mutual respect, and the avoidance of extremism in practicing religion. This study aims to examine the role of student management in implementing the values of religious moderation in schools. A descriptive qualitative approach is used to provide a detailed overview of how planning, organizing, implementation, and evaluation in student management relate to the implementation of religious moderation in schools. The methods used in this study include interviews, observation, and documentation. The results show that the planning aspect of student management includes efforts to integrate religious moderation values through extracurricular curricula and religious activities. The implementation of religious moderation programs is carried out through activities such as discussions, seminars, and interfaith collaboration. The organizational process begins with an analysis of the current condition of students. This step is essential for understanding the students' situation and needs, allowing for more targeted programs. This research contributes to Islamic education by promoting a more inclusive educational environment.